PEMBERDAYAAN PEREMPUAN DAN ALUMNI KEBIDANAN DALAM MERINTIS USAHA BARU BERBASIS RISET DENGAN HOME PRODUKSI BISKUIT KELOR (MORINGA OLEIFERA) DI KELURAHAN MANNURUKI KOTA MAKASSAR - Sitti Mukarramah; Zulaeha Amdadi (Bajang Institute, 2022)
The world of work demands that its employees must have higher skills in order to be able to face global developments due to fierce competition. That in the world of work unemployment continues to increase every year, especially unemployment from college graduates. Therefore, undergraduate candidates are required to be more creative, innovative, have competence, job skills, and good personality. The approach taken in this community service activity is to develop and enhance an entrepreneurial spirit in starting new business. The solution offered to solve the problem is to increase marketing management knowledge in starting new businesses. The outputs produced are proceedings, leaflets and home production of Moringa Biscuits. The targets of this activity are women and alumni of the Department of Midwifery in the work area of the Puskesmas Mangasa Makassar, with the target of increasing knowledge in entrepreneurship.